Merleau-Ponty and Derrida : intertwining embodiment and alterity - Reynolds, Jack (Series in Continental thought, 2004)
"While there have been many essays devoted to comparing the work of Maruice Merleau-Ponty with that of Jacques Derrida, there has been no sustained book-length treatment of these two French philosophers. Additionally, many of the essays presuppose an oppositional relationship between them, and between phenomonology and deconstruction more generally." "Jack Reynolds systematically explores their relationship by analyzing each philosopher in terms of two important and related issues - embodiment and alterity. Focusing on areas with which they are not commonly associated (e.g., Derrida on the body and Merleau-Ponty on alterity), he makes clear that their work cannot be adequately characterized in a strictly oppositional way."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.